SYMGERBI (CIPEEX, 2022)
HEALTH SERVICE WASTE, COMMONLY ASSOCIATED WITH THE TERM HOSPITAL WASTE OR HOSPITALWASTE, IS THE NAME GIVEN TO WASTE ORIGINATING FROM MEDICAL ACTIONS DEVELOPED IN HEALTH CAREUNITS, IN PREVENTION, DIAGNOSIS, TREATMENT, REHABILITATION AND RELATED RESEARCH ACTIVITIES. WITHHUMANS OR ANIMALS, IN PHARMACIES, IN MEDICO-LEGAL ACTIVITIES, IN TEACHING AND IN ANY OTHERACTIVITIES THAT INVOLVE INVASIVE PROCEDURES. THIS WORK AIMED AT THE STUDY AND CREATION OF ASOFTWARE WITH THE OBJECTIVE OF PROVIDING A MORE AGILE FORM OF ORDER TO CORRECTLY DISCARD THEGARBAGE, FAVORING COMMUNICATION BETWEEN HOSPITALS AND CLINICS WITH THE RESPONSIBLE COMPANY.THE PROJECT HAS AN OBJECTIVE A SEARCH FOR SIMPLICITY FOR COLLECT, IN VIEW OF THE USE OF METHODSSUCH AS LEAN INCEPTION AND A BETTER UNDERSTANDING OF THE PRODUCT SO THAT USERS HAVE GREATEREASE AND AGILITY, WITHOUT CAUSING A DROP IN PERFORMANCE IN THE PRODUCT OR IN THE DEVELOPMENT. ITIS ALSO EXPECTED THAT THE ENTIRE TOOL DEVELOPMENT PROCESS SEEKS TO BRING A BETTER EXPERIENCE TOTHE JOB MARKET. AS IT IS IN ITS INITIAL PHASE, TOOLS WERE USED FOR PLANNING SUCH AS: BPMN, WHERETHERE WAS AN ATTEMPT TO OUTLINE THE BASIC FUNCTIONALITIES OF THE FIRST PROTOTYPE, THE DISCUSSIONAND DEFINITION OF FUNCTIONAL AND NON-FUNCTIONAL REQUIREMENTS AND BUSINESS RULES WAS ALSOCARRIED OUT, IN ADDITION TO THE COMPOSITION OF A PERSONA IN ORDER TO BETTER DIRECT THE CREATION OFTHE SOFTWARE, THE DESIGN OF THE PAGES, LAYOUT AND COLORS, ALWAYS KEEPING IN MIND THE NEEDS OFTHE CLIENT, SEEKING TO FACILITATE UNDERSTANDING AND REDUCE THE EFFORT ON THE PART OF THE CLIENT.AFTER BE NOTICED THE LACK OF INFORMATION ABOUT THIS TYPE OF CONTENT, THE GREAT NEED TO TALK ABOUTPROBLEMS CAUSED BY HOSPITAL WASTE, MAINLY DUE TO THE SARS COV-2 (COVID 19) PANDEMIC,AND WITH RECENT DISCUSSIONS ON THE SUBJECT, THERE WAS A CONCLUSION OF THE DEVELOPMENT OF ASOFTWARE FOR IN ORDER TO PROVIDE A SIMPLER AND MORE AGILE COMMUNICATION BETWEEN HOSPITALSAND COMPANIES SPECIALIZED IN TRANSPORT AND DISPOSAL, WITH THE AIM OF NO LONGER HAVING SCENESOF SOMETHING SO DANGEROUS LEFT ANYWHERE. THE INITIAL IDEA WAS JUST THE CREATION OF A WEBSITE,WHERE THE DISPOSAL COMPANY AND HOSPITALS COMMUNICATED, BUT AS THE CONVERSATIONSPROGRESSED, THE NEED TO NEGOTIATE DISPOSAL WAS REALIZED IN ORDER NOT TO LET THE DISPOSAL OCCURINCORRECTLY. AFTER SEVERAL DISCUSSIONS, IT WAS CONCLUDED THAT THE BEST WAY TO LINK THE PERSONRESPONSIBLE FOR CREATING THE INFECTIOUS WASTE WITH THE PERSON RESPONSIBLE FOR DESTROYING ITWOULD BE TO CREATE A WEBSITE WHERE HOSPITALS, CLINICS, PET SHOPS COULD REGISTER AND FROM THEREREQUEST THE COLLECTION OF GARBAGE, AND THE CREATION OF A PROGRAM WHERE THE INCINERATOR WOULDRECEIVE THIS REQUEST ALONG WITH THE APPLICANT'S INFORMATION, SUCH AS ADDRESS, TYPE OF WASTE, ANDAPPROXIMATE QUANTITY.
Keywords: lixo; descarte; desenvolvimento; software.